Juxtaglomerular Cell Tumor (Reninoma): A Case Report and Mini-Review - ŞEKERCİ, ÇAĞRI AKIN; FİLİNTE, DENİZ; ŞENER, TARIK EMRE; TANIDIR, YILÖREN; CİNEL, ZELİHA LEYLA (AVES PRESS LTD, 2016)
Reninomas are rare tumors derived from juxtaglomerular cells. Here, we report a case of a 17-year-old male patient who presented to our outpatient clinic with secondary hypertension and flank pain. Initial work-up revealed hypokalemia, and magnetic resonance imaging (MRI) revealed a solid lesion as a 4.8x4.8-cm contrast-enhanced exophytic mass. He underwent open nephron-sparing surgery, and the lesion was excised. The pathological study revealed a juxtaglomerular cell tumor (reninoma). Shortly after the surgery, all medications were withdrawn, and his blood pressure and hypokalemia normalized. This case can lead physicians to better understand the importance of the management of reninomas as a curable cause of secondary hypertension and also points out the importance of diagnostic care.
Keywords: Reninoma; secondary hypertension; nephron-sparing surgery; diagnostics